2013
DOI: 10.4067/s0717-95022013000400036
|View full text |Cite
|
Sign up to set email alerts
|

Evaluation of Three Mathematical Functions to Describe the Relationship Between Body Weight, Body Condition and Testicular Dimensions in Yankasa Sheep

Abstract: SUMMARY:Body size and testicular measurements have been found to be important parameters utilized in breeding soundness evaluation. The present study therefore, aimed at determining the relationship between body weight (BW), body condition score (BCS), testicular length (TL), testicular diameter (TD) and scrotal circumference (SC) in 120 extensively reared Yankasa rams (approximately 30 months old) using linear, quadratic and cubic predictive models. Coefficient of determination (R 2 ), Adjusted R 2 , the esti… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
4
0

Year Published

2016
2016
2021
2021

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 10 publications
(5 citation statements)
references
References 24 publications
1
4
0
Order By: Relevance
“…The best fitting models found in our study were also determined to be the best fitting ones in rams in the study by Yakubu and Musa-Azara (2013). For instance, these authors reported estimation of body weight from testicle length and diameter appeared to be better under the cubic model based on higher R 2 values.…”
Section: Gsi Modellingsupporting
confidence: 72%
“…The best fitting models found in our study were also determined to be the best fitting ones in rams in the study by Yakubu and Musa-Azara (2013). For instance, these authors reported estimation of body weight from testicle length and diameter appeared to be better under the cubic model based on higher R 2 values.…”
Section: Gsi Modellingsupporting
confidence: 72%
“…Phenotypic correlation between body weight and age (weeks) was computed separately for birds on deep litter and those kept in cages. The relationship between body weight and age was also established using Linear and Quadratic regression models and these were fitted as described in Yakubu and Muza-Azara [18]. The Goodness of fit was determined using the coefficient of determination (R 2 ), adjusted R 2 , mean square error (MSE) and root mean square error (RMSE).…”
Section: Discussionmentioning
confidence: 99%
“…The findings of this study is also in line with the report of (Cankaya et al, 2014) who noted that cubic regression model gave best values when comparing with other models for the first lactation curve of jersey cows. Yakubu et al, (2013) also reported that cubic model appeared to produce better goodness of fit when traits are considered singly. The result also agreed with the report of Druet et al, (2003) and Silvestre et al, (2006) who used the Wood models and cubic spline regression models for modeling lactation curves.…”
Section: Resultsmentioning
confidence: 94%